2017
DOI: 10.5195/jyd.2017.497
|View full text |Cite
|
Sign up to set email alerts
|

Urban Youth Perceptions of Agriculture

Abstract: To change public perceptions, particularly from urban populations, of agriculture and natural resources (ANR) fields, the University of Tennessee developed a model of strategic educational recruitment to extend beyond traditional college fair experiences to educate underrepresented candidates. The High School Agricultural Education Initiative (HSAI) provided 10 th -grade students with opportunities to: (a) gain knowledge of and appreciation for disciplines in agriculture and natural resources, (b) learn about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Fischer and Burton [11] argued that farm inheritance, as a socially constructed phenomenon, requires continuous participation in agricultural production and the socialization of farm heirs from early childhood to develop an 'heir identity', which influences the youth's internal drive to take over the family farm. Their findings are consistent with those of Jean-Philippe et al [12], who believed that rural youths' mastery of agricultural skills affects their attitudes toward agriculture. Furthermore, rural land provides basic living security for rural residents in the form of agricultural production, which is the foundation of rural areas [7].…”
Section: Introductionsupporting
confidence: 91%
“…Fischer and Burton [11] argued that farm inheritance, as a socially constructed phenomenon, requires continuous participation in agricultural production and the socialization of farm heirs from early childhood to develop an 'heir identity', which influences the youth's internal drive to take over the family farm. Their findings are consistent with those of Jean-Philippe et al [12], who believed that rural youths' mastery of agricultural skills affects their attitudes toward agriculture. Furthermore, rural land provides basic living security for rural residents in the form of agricultural production, which is the foundation of rural areas [7].…”
Section: Introductionsupporting
confidence: 91%
“…This situation translates into a lack of knowledge or background in the primary sector among youths (Jean-Philippe et al, 2017;blind for review). Previous studies have concluded that early exposure to agricultural experiences and career paths during the middle and high school years can be a critical element toward positively influencing the agricultural perceptions and attitudes of youth (Jean-Phillipe et al, 2017).…”
Section: Agriculture Prestige Among Youthmentioning
confidence: 99%
“…Interestingly, the objective factors associated with youths' negative stereotypes about agriculture stem from studies with those living in urban areas (Jean-Philippe et al, 2017;Tiraieyari and Krauss, 2018). Still, some parallel findings have indicated that rural youths, including rural NEETs, may also develop negative images about agriculture based on the lack of resources (land), knowledge or experience (Nag et al, 2018; blind for review).…”
Section: Agriculture Prestige Among Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, demographics play a key role in the perception of technology use, in that millennials are more concerned about the effects of biotechnology on the economics (specifically price) of food more than other groups of people (CCFI 2019). Furthermore, it has been suggested that high schools could benefit the most from funding the integration of science curriculum into agriculture programs, and possibly vice versa (Myers and Washburn 2008), or commencing agricultural education programs, which has proven effective at increasing students' knowledge in urban schools (Jean-Philippe et al 2017). Both these strategies to inform younger Canadians could increase the positive perception of the industry and biotechnology.…”
Section: Introductionmentioning
confidence: 99%